Devolution Commissions in the shadow of Whitehall: the Smith Commission and the creation of a 'Powerhouse Parliament'. Issue 4 (3rd December 2018) - Kenealy, Daniel; Parry, Richard
Abstract In the UK, it has become common for commissions to be convened to recommend changes to the devolved settlements in Scotland and Wales. The most recent of these commissions was the Smith Commission, convened in September 2014 to agree on a new package of powers for the Scottish Parliament. In this article, we investigate the Smith Commission, offering both a first cut history of a pivotal moment in the UK's constitutional development, and a case study that sheds new light on the workings of such commissions, on the culture and practices of civil servants, and on power dynamics both within Whitehall and between Whitehall and devolved governments. We set down a marker for what we hope will be the further comparative study of such commissions.